2022
DOI: 10.15252/embj.2021108780
|View full text |Cite
|
Sign up to set email alerts
|

Schwann cell precursors represent a neural crest‐like state with biased multipotency

Abstract: Schwann cell precursors (SCPs) are nerve-associated progenitors that can generate myelinating and non-myelinating Schwann cells but also are multipotent like the neural crest cells from which they originate. SCPs are omnipresent along outgrowing peripheral nerves throughout the body of vertebrate embryos. By using single-cell transcriptomics to generate a gene expression atlas of the entire neural crest lineage, we show that early SCPs and late migratory crest cells have similar transcriptional profiles charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 150 publications
6
60
1
Order By: Relevance
“…The D14 cluster (C7) was characterised by sympathoadrenal/autonomic progenitor markers (GATA3, ASCL1 40,41 ). Cells at D19 consisted of three distinct fractions with mature SCP-like (cluster C8; CRYAB, POSTN, and IGFBP5 42 ), with sympathoblast-like (C11; PHOX2A/B, ELAVL4 16,43 ), or with mesenchymal (C9; COL1A1, FN1) features, in line with findings showing that trunk NC and SCPs are competent to generate mesenchyme 42,44,45 . A fourth cluster (C10) exhibited both sympathoblast and mesenchymal features, suggesting a bridge between cell identities.…”
Section: Differentiation Of In Vitro-derived Human Trunk Nc Cells Rev...supporting
confidence: 83%
“…The D14 cluster (C7) was characterised by sympathoadrenal/autonomic progenitor markers (GATA3, ASCL1 40,41 ). Cells at D19 consisted of three distinct fractions with mature SCP-like (cluster C8; CRYAB, POSTN, and IGFBP5 42 ), with sympathoblast-like (C11; PHOX2A/B, ELAVL4 16,43 ), or with mesenchymal (C9; COL1A1, FN1) features, in line with findings showing that trunk NC and SCPs are competent to generate mesenchyme 42,44,45 . A fourth cluster (C10) exhibited both sympathoblast and mesenchymal features, suggesting a bridge between cell identities.…”
Section: Differentiation Of In Vitro-derived Human Trunk Nc Cells Rev...supporting
confidence: 83%
“…We found that MITF was present in nerves in what are likely Schwann cell precursors (white arrows in Fig. 8A) as shown by Adameyko's lab (Adameyko et al, 2009;Kastriti et al, 2022). What we observed in our immunostaining was that MITF expression was found along peripheral nerves, but along all its length as acetylated tubulin was, thus it was not complete overlap with acetylated tubulin that stains axons (white arrows in Fig.…”
Section: Labeling Of Trunk Neural Crest Cells and Its Derivativessupporting
confidence: 63%
“…2) Another character is the rapid rostrocaudal progression of TNCC migration and development observed for the Egyptian cobra was the same of the colubrid snake. 3) The presence of MITF in Schwann cell precursors along developing nerves, which suggests that reptile Schwann cell precursors could have the same multipotency as mammalian migrating NCC and thus give rise to its varied derivatives (Kastriti et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, glial and Schwann cell lineage specific markers are upregulated [ 1 ]. Nevertheless, Schwann cell precursors retain a high degree of multipotency, and become primed towards immature Schwann cells or other fates in a gradual manner [ 55 , 62 ].…”
Section: In Vivo Development Of Schwann Cellsmentioning
confidence: 99%